Cortical interneurons migrating on a pure substrate of N-cadherin exhibit fast synchronous centrosomal and nuclear movements and reduced ciliogenesis - Luccardini, Camilla; Leclech, Claire; Viou, Lucie; Rio, Jean-Paul; Métin, Christine (Frontiers in Cellular Neuroscience, 2015)
The embryonic development of the cortex involves a phase of long distance migration of interneurons born in the basal telencephalon. Interneurons first migrate tangentially and then reorient their trajectories radially to enter the developing cortex. We have shown that migrating interneurons can assemble a primary cilium, which maintains the centrosome to the plasma membrane and processes signals to control interneuron trajectory (Baudoin et al., 2012). In the developing cortex, N-cadherin is expressed by migrating interneurons and by cells in their migratory pathway. N-cadherin promotes the motility and maintains the polarity of tangentially migrating interneurons (Luccardini et al., 2013). Because N-cadherin is an important factor that regulates the migration of medial ganglionic eminence (MGE) cells in vivo, we further characterized the motility and polarity of MGE cells on a substrate that only comprises this protein. MGE cells migrating on a N-cadherin substrate were seven times faster than on a laminin substrate and two times faster than on a substrate of cortical cells. A primary cilium was much less frequently observed on MGE cells migrating on N-cadherin than on laminin. Nevertheless, the mature centriole (MC) frequently docked to the plasma membrane in MGE cells migrating on N-cadherin, suggesting that plasma membrane docking is a basic feature of the centrosome in migrating MGE cells. On the N-cadherin substrate, centrosomal and nuclear movements were remarkably synchronous and the centrosome remained near the nucleus. Interestingly, MGE cells with cadherin invalidation presented centrosomal movements no longer coordinated with nuclear movements. In summary, MGE cells migrating on a pure substrate of N-cadherin show fast, coordinated nuclear and centrosomal movements, and rarely present a primary cilium.